The Effectiveness Of Audiovisual About Danger Signs Of Pregnancy With Pregnant Women's Knowledge - Sindi, Dwi Puspita; Mediarti, Devi; Hindun, Siti (Poltekkes Kemenkes Palembang, 2022)
Background : One of the factors causing the high maternal mortality rate (MMR) is the lack of knowledge of pregnant women about the danger signs of pregnancy. Recognizing the danger signs of pregnancy has an important role to prevent or reduce the Maternal Mortality Rate (MMR). It is very important to know so that the danger signs can be prevented, because if the danger signs are known early, the treatment will be faster. Providing audiovisuals in the form of videos about the danger signs of pregnancy to pregnant women is one way to increase knowledge, so that pregnant women can quickly make decisions when they encounter danger signs of pregnancy. Objective : This study aims to determine the effectiveness of audiovisual about pregnancy danger signs on the knowledge of pregnant women at PMB Choirul Mala, Palembang City in 2021. Method : This research used pre-experimental one group pretest- posttest design. Sample were taken from the population that met the inclusion criteria, with 30 people with total sampling. Result : The results of the study using the test test obtained a significance value of 0.000 (ρ <0.05), meaning that there was a significant difference between increasing knowledge of pregnant women before and after being given audiovisuals. Conclusion : There is audiovisual effectiveness about the danger signs of pregnancy on increasing knowledge of pregnant women at PMB Choirul Mala in 2021. Suggestion : The result of the study can be used as asource of information to reduce the danger signs of pregnancy in pregnant women and be applied in maternity midwifery services. Keywords : Audio visual, pregnancy danger signs, knowledge, pregnancy.